Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Aritmetika Sosial Berdasarkan Teori Newman - Reskina, Reskina; Kartini, Kartini (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The purpose of this study was to analyze students' errors in solving social arithmetic problems using Newman's theory (NEA). The research method used is descriptive qualitative research. The research subjects were 15 class VII students of SMPN 1 Bangun Purba. The data collection technique was carried out by a written test. The test instrument used is a matter-based test on the ability to solve mathematical problems on social arithmetic material. The instrument used is in the form of 4 questions in the form of descriptions that have been tested for their validity, reliability, discriminating power, and index of difficulty. The research was conducted in the even semester of the 2021/2022 school year. The results of the study showed that the most frequent errors made by students were errors in concluding the final answer (encoding error). This happens when students do not make conclusions even though they have received answers. Based on data analysis, the percentage of reading errors was 12.00%, understanding errors were 19.33%, transformation errors were 23.33%, process skill errors were 18.67%, and final answer errors were 26.67%. The causes of errors that occur include students not being able to use the right formula in solving problems, careless in doing calculations and students not making conclusions at the end of the answer.